News in Early Modern Europe Currents and Connections - Davies, Simon; Fletcher, Puck (Brill, 2020)
News in Early Modern Europe - Currents and Connections, edited by Simon Davies and Puck Fletcher, presents significant new research on the production and dissemination of news in early modern Europe. Interdisciplinary in focus, and wide in geographical and chronological scope, the collection includes theoretical enquiries about the nature of news alongside deep archival case studies.